Authority and Procedures for Determination of the Foundation Managers - I Made Arjaya; Ni Wayan Umi Martina; Ida Bagus Erwin Ranawijaya (Sociological Jurisprudence Journal, 2018)
The purpose of this study is to find out who is authorized and how the procedure of determination the foundation managers. The method used in this research is the method of normative legal research with statute approach, conceptual approach and case approach. Research location in Denpasar Bali. Sources of legal material are legislation, and cases faced by the DJ foundation. How to collect legal materials is to use the card system. The result of the research is the authority to determination the foundation managers by the foundation trustees and the procedures of determination the foundation managers begins with the supervision conducted by the supervisor of the foundation, followed by the temporary dismissal, then proceed with clarification meeting from the managers of foundation, which can lead to the determination of the foundation managers.